PENGARUH KONSENTRASI GELATIN DAN SIRUP GLUKOSA TERHADAP SIFAT KIMIA DAN SENSORIS PERMEN JELLY SARI BUAH PALA (Myristica fragrans Houtt) - Berandon Nelwwan; Tineke Langi; Teltje Koapaha; Thelma Tuju (COCOS, 2015)
ABSTRACTDevelopment of local product is very important to improve the potency local product. Nutmeg is one of fruit from North Sulawesi. The highest of harvest rate is not balance than product from nutmeg fruit especially meat of fruit. Jelly candy is one of candy made from water or juice and gel agent, that have clear appearance and have jelly texture. Gelatin is a food additive that required in making of jelly candy, so was glucose. The aims of this research are to determine the correct concentration of gelatin and glucose syrup, to analyze the chemical components in jelly candy and to analyze the organoleptic test of jelly candy. This research has used RAL method with 2 factors, which A factor is gelatin concentration and B factor is glucose syrup. The result of this research is the 20% of gelatin and 60% of glucose syrup has 19,60% water content, 0,79% ash and 14,22% sucrose reduction which already match with the standards (SNI). The 20% of gelatin and 60% of glucose syrup has a neutral color, delight taste, neutral color and delight texture.Keywords: nutmeg, gelatin, glucose syrup, jelly candy.